Insights on pediatric medication initiation: perceptions of caregivers and children - Rubio-Valera, Maria; Carbonell-Duacastella, Cristina; Peñarrubia-María, Maite; Pacheco, Eva; Gabriela-Ricciardeli, Patricia; Aznar-Lou, Ignacio; Gil-Girbau, Montserrat (Frontiers in Pharmacology, 2025)
IntroductionChildren fail to initiate a high proportion of medications but little is known about motivations for non-initiation.ObjectiveTo explore the factors affecting the decision to initiate a medication prescribed to children from caregivers’ and children’s perspectives.MethodsQualitative study based on Grounded theory using a constructivist approach. Twenty-one caregivers and six children (<18 years old) were individually interviewed between 2021 and 2022 in Spain using a semi-structured thematic guide. Interviews were transcribed and analyzed by pharmacists, pediatricians and family physicians through a constant comparative analysis and results were internally audited.ResultsCaregivers and healthcare professionals are the central figures involved in the decision-making process regarding treatment initiation; children were rarely involved. Caregivers, usually mothers, made a risk-benefit evaluation based on the perception of the disease and the medication, which was influenced by intrapersonal factors (emotional burden, health literacy and stigma); children-related factors (age, treatment and emotional burden); and factors related to the professionals (accessibility, discourse alignment, information, respect and emotional support, trust and specialty); healthcare system (trust and use of e-consultations) and context (media, peer pressure and social stigma).ConclusionThe decision to initiate medication in the pediatric population is multifactorial and influenced by perceptions on the disease and treatment, intrapersonal factors related to the caregivers and children, and interpersonal factors and factors related to the healthcare system and contexts. An informed, shared decision-making process that considers both the participation of children and the needs for support from caregivers when prescribing a treatment could promote initiation in the pediatric population.